Policy Polemic for Covid 19 and Efforts to Handling Information Technology - Sri Pujiningsih (Journal of Morality and Legal Culture, 2020)
The Covid 19 pandemic case is sweeping the world, including one of them affected by the virus outbreak, the State of Indonesia. In dealing with this virus outbreak, each country takes different strategies. The Indonesian State pursues a large-scale social restriction policy. This study aims to explain the Covid 19 policy polemic and the efforts to handle it. The research method uses a normative juridical approach because it examines government policies in handling Covid cases, namely Law No.6 of 2018 and Government Regulation No.21 of 2020. Efforts to handle them, the government needs action that is fast and effective in dealing with the rate of spread of the Corona virus.